Pengaruh Perang Dunia Kedua Terhadap Kemajuan Jepang pasca Perang Dingin - Suniyyah Puspita Sari; Ulya Fatimatuzzahra (ADALAH, 2021)
The end of World War II led to several changes to the global world order, including japan. The often inferior eastern country motivated Japan to make some progress for its country in World War II, but its defeat led to its misfortune as well as its fortune as a superpower in the field of industrial technology. The economy is the most targeted by the Japanese state in building the progress of the country, especially in the field of science and industrial technology. Post-World War II Japan also experienced changes in Japan's post-World War II Foreign Policy, stemming from several doctrines produced by its Prime Minister, such as the Yoshida Doctrine which focused on economic development, then there was the Fukuda Doctrine which focused on Japanese foreign policy to Southeast Asia. Japan's progress in competing with other western countries, is also supported by the principle of group work and the delivery of a number of academics who are ready to serve their country.